Amelioration technology for soil sustainability - Rathoure, Ashok K., 1983- (Engineering Science Reference, 2019)
"This book provides the latest and practical guideline to readers working in the field of soil sustainability and crop yield. It also examines characteristics of various soil amendments, hydrophobic soil amelioration, nutrient solubilizing microorganisms, the impact analysis of amendment application, and recent advances on soil liming "--